FAKTOR-FAKTOR YANG MEMENGARUHI KUALITAS LAPORAN KEUANGAN (Media Riset Akuntansi, 2022)
This study aims to examine the effect of applying accounting information systems, internal control systems, and accountability to the quality of financial reports at the Office of the General Elections Commission of the City of Jakarta, Central Jakarta Administration in providing the best information presented to the public so as to increase the level of public confidence in the quality of financial statements presented. The sampling technique in this study uses the census method. The analytical method used is SmartPLS to test hypotheses. The samples used in this study were eighty eight employees of the Office of the General Election Commission (KPU), members of the district election committee (PPK) and members of the voting committee (PPS) who had worked for at least five years at the Office of the General Election Commission of the City Administration Jakarta Center. The results of the study either simultaneously or partially support the hypothesis that the application of accounting information systems, internal controls, and accountability affects the quality of financial reports at the Office of the General Elections Commission of the City of Jakarta, Central Jakarta Administration.